IMMUNE RESPONSES IN VITRO : II. SUPPRESSION OF THE IMMUNE RESPONSE IN VITRO BY SPECIFIC ANTIBODY - Pierce, Carl W. (The Rockefeller University Press, 1969)
The effects of hyperimmune anti-sheep erythrocyte (SRBC) antibody on the plaque-forming cell (PFC) response to SRBC by mouse spleen cells in vitro were studied. Anti-SRBC antibody specifically suppressed the PFC response against SRBC. The degree of suppression was directly related to the amount of antibody added and was overcome by large amounts of antigen. Suppressive activity was absorbed from the sera by SRBC and could be partially eluted from the antigen by heat. The PFC response in cultures stimulated with antigen-antibody complexes prepared with high concentrations of antibody were suppressed; however, some complexes prepared at lower antibody concentrations stimulated greater responses than SRBC alone. Antibodies collected after four immunizations had greater suppressive ability than those collected after two immunizations. The degree of suppression was as great whether antibody was added at the initiation of the cultures or 24 hr later, suggesting that during the first 24 hr the culture system was antigen-dependent. Incubation of separated lymphoid cells with antibody did not impair their ability to develop a PFC response in vitro. However, if macrophages were incubated with antibody either before or after incubation with SRBC, the subsequent PFC response by lymphoid cells was suppressed. The data are consistent with the conclusion that antibody suppresses the PFC response in vitro by neutralizing the antigenic stimulus at the macrophage-dependent phase of the response.